Checklist of large and medium-bodied mammals from four areas of Tocantins state, Central Brazil - Mercês, Michelle Pinto; Alves-Silva, Kleiton Rodolfo; de Paula, Wlainer Silva (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2020)
The state of Tocantins is located in Central Brazil. The northern extreme of this state corresponds to the southeastern portion of the Amazon biome, while it is covered primarily by Cerrado savanna, as well as the transition area between these two biomes. We provide a checklist of large- and medium-bodied mammals from four localities in Tocantins, update the list of species for the state, and compile the available information on their geographic distribution. We surveyed mammals at four sites during different periods (between 2010 and 2018), using camera traps and opportunistic observations. In spite of the differences in the sampling effort among the sites, we recorded 42 mammal species belonging to eight orders and 20 families. Our list includes rare and threatened species, such as the jaguar (Panthera onca), the giant anteater (Myrmecophaga tridactyla), and the lowland tapir (Tapirus terrestris). One species (Galictis cuja) was recorded in the state for the first time and the known range distribution of two others (Speothos venaticus and Alouatta caraya) was updated.